A novel therapy strategy for bile duct repair using tissue engineering technique: PCL/PLGA bilayered scaffold with hMSCs. (25th February 2015) - Zong, Chen; Wang, Meicong; Yang, Fuchun; Chen, Guojun; Chen, Jiarong; Tang, Zihua; Liu, Quanwen; Gao, Changyou; Ma, Lie; Wang, Jinfu
Abstract: The current clinical treatments for complications caused by hepatobiliary surgery still have some inevitable weakness. The aim of the study was to fabricate a tissue‐engineered bile duct that utilized a novel bilayered polymer scaffold combined with human bone marrow‐derived mesenchymal stem cells (hMSCs) for new treatment of biliary disease. The biocompatibility of polycaprolactone (PCL) (PCL)/poly(lactide‐co‐glycolide) (PLGA) scaffold with hMSCs was first examined, and the hMSC–PCL/PLGA constructs (MPPCs) prepared. The MPPCs and blank scaffolds were then transplanted into 18 pigs for evaluation its efficacy on bile duct repairing, respectively. In vitro, the PCL/PLGA scaffold was verified to support the adhesion, proliferation and matrix deposition of hMSCs. There was no sign of bile duct narrowing and cholestasis in all experimental animals. At 6 months, the MPPCs had a superior repairing effect on the bile duct injury, compared with the blank PCL/PLGA scaffolds. Therefore, the implanted scaffolds could not only support the biliary tract and allow free bile flow but also had direct or indirect positive effects on repair of injured bile duct. Copyright © 2015 John Wiley & Sons, Ltd.